2012
DOI: 10.1007/s00705-012-1466-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterisation of rabies virus strains in the Republic of Macedonia

Abstract: Rabies, a worldwide zoonosis, remains a public-health concern despite oral wildlife vaccination in Europe. After a ten-year break, Macedonia reported eight rabies cases in 2011-2012. Two countries (Serbia and Bulgaria) bordering Macedonia are reporting cases in domestic and wild animals. This report describes the genetic characterisation of eight isolates from Macedonia compared with representative samples from neighbouring countries. All of the isolates tested belong to the Eastern European group, with a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…JF973785). This perfect nucleotide identity shown with the Serbia isolate collected >15 years ago suggests the persistence of some viral strains over time in the Balkans, in accordance with previous studies ( 4 , 9 ). Amino acid identity was perfect among all 9 isolates from Greece.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…JF973785). This perfect nucleotide identity shown with the Serbia isolate collected >15 years ago suggests the persistence of some viral strains over time in the Balkans, in accordance with previous studies ( 4 , 9 ). Amino acid identity was perfect among all 9 isolates from Greece.…”
supporting
confidence: 91%
“…Greece shares land borders with Turkey, Former Yugoslav Republic of Macedonia (FYROM), and Bulgaria, where rabies is reported in wild and domestic animals ( 4 ; www.who-rabies-bulletin.org/). After the fox rabies case reported in FYROM in 2011, ≈0.3 km from Greece ( 4 ), rabies surveillance was improved along the northern and eastern land borders of Greece, and wild and domestic animals found dead or suspected of having rabies were collected.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiologic studies of rabies dynamics have suggested westward and southward spread in the Balkan peninsula. Surveillance varies by country and over time, meaning that although these recent epidemics are likely reintroductions, there is potential for undetected, low-level rabies persistence in some areas (Johnson et al 2007;McElhinney et al 2011;Picard-Meyer et al 2013;Muller et al 2015).…”
Section: Rabies Virus Infection By Dan Hortonmentioning
confidence: 99%
“…Greece borders with Albania, Former Yugoslav Republic of Macedonia (FYROM), Bulgaria and Turkey. In the last three countries, rabies has been reported in wild and domestic animals and wildlife vaccination campaigns using oral live-attenuated vaccines have been implemented most recently: in Bulgaria since 2009, in FYROM since 2011 and in Turkey since 2008 [4–6]. Despite successful oral vaccination campaigns of wildlife targeting the elimination of rabies in large parts of Europe [1], the disease still occurs in the continent and, in 2012, 4884 cases were diagnosed in animals.…”
Section: Introductionmentioning
confidence: 99%